Analysis of Meteorological Fluctuations and Long-Term Drought Assessment in the Southern Coasts of Iran: An Observational and Climate Modeling Approach - Seyed Hassan Alavinia; Mahdi Salmanpour; Atefeh Abkar (اکوهیدرولوژی)
Research Topic: This study analyzes drought trends at five synoptic stations along the southern coast of Iran (Bandar Abbas, Bandar Lengeh, Bushehr, Chabahar, and Kish) using the Standardized Precipitation Index (SPI) at two temporal scales: 12-month (short-term) and 48-month (long-term). Method: In this study, five synoptic stations in the southern region of Iran were selected. For the observational data spanning the period 1985–2021, the 12-month (SPI-12) and 48-month (SPI-48) Standardized Precipitation Indices were calculated, and seasonal and multi-year drought and wetness patterns were identified. Subsequently, future precipitation for the period 2023–2043 was projected under two climate change scenarios—the optimistic (SSP1-2.6) and pessimistic (SSP5-8.5) scenarios of the CMIP6 project—using the MPI-ESM1.2-HR climate model and the SDSM. The corresponding SPI indices were then computed. For drought monitoring, the SPI was calculated at 12- and 48-month scales for both observational data and the projected data using the SPEI package in R software. Results: The overall trend of drought and wet periods indicates that severe drought events occurred at the Bandar Abbas station in the years 1994, 2000, and 2012. In contrast, severe wet periods were observed in this station in 1988, 1990, and 2007. Similar conditions were recorded at the Bandar Lengeh station, with severe droughts in 1987, 2003, and 2011 and severe wet periods in 1990, 1998, and 2006. The Bushehr and Kish stations exhibited analogous patterns, with severe wet periods in 1990, 1998, and 2006 and droughts in 1987, 2003, and 2011. Notably, the year 1994 marked extreme conditions for all stations, while 1990 was characterized by wet periods across all five stations. Regarding future projections, the results indicate that under the SSP5-8.5 scenario, the intensity of drought is more pronounced in the western stations compared to the eastern stations. The 12-month SPI reveals more rapid fluctuations in drought conditions, making it suitable for assessing seasonal or annual droughts. Conclusions: The analysis of the SPI (Standardized Precipitation Index) with observational data demonstrated that drought patterns in this region are complex and influenced by multiple factors, including changes in atmospheric systems, oceanic circulation patterns, and human activities. The projections of this study suggest that under the SSP5-8.5 scenario, the southern coastal regions of Iran will face a significant increase in the intensity and frequency of droughts. The findings of this research have important implications for water resource management and regional planning in southern Iran. Given the predicted rise in drought intensity and frequency, adopting adaptation measures such as developing early drought warning systems, improving water resource management, enhancing water use efficiency, modifying cropping patterns, promoting drought-resistant agriculture, diversifying economic resources to reduce reliance on agriculture, and raising public awareness about droughts and adaptation strategies is essential to mitigate the adverse effects of this phenomenon.